2022
DOI: 10.1088/1748-3190/ac42e2
|View full text |Cite
|
Sign up to set email alerts
|

Fully-printed metamaterial-type flexible wings with controllable flight characteristics

Abstract: Insect wings are an outstanding example of how a proper interplay of rigid and flexible materials enables an intricate flapping flight accompanied by sound. The understanding of the aerodynamics and acoustics of insect wings have enabled the development of man-made flying robotic vehicles and explained basic mechanisms of sound generation by natural flyers. This work proposes the concept of artificial wings with a periodic pattern, inspired by metamaterials, and explores how the pattern geometry can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The shape and the structure of the wing are important as governing its structural, aerodynamic and acoustic characteristics 10,18,27 . Therefore, we accurately reproduced the in-plane configuration of veins and membranes, while the out-of-plane structure can be simplified by assuming a uniform varying thickness from 0.45 mm to 0.1 mm (Figure 1, right) 18,28 . The top of the wing is thus naturally reinforced by its three-dimensional structure.…”
Section: Model Of a Wingmentioning
confidence: 98%
“…The shape and the structure of the wing are important as governing its structural, aerodynamic and acoustic characteristics 10,18,27 . Therefore, we accurately reproduced the in-plane configuration of veins and membranes, while the out-of-plane structure can be simplified by assuming a uniform varying thickness from 0.45 mm to 0.1 mm (Figure 1, right) 18,28 . The top of the wing is thus naturally reinforced by its three-dimensional structure.…”
Section: Model Of a Wingmentioning
confidence: 98%
“…[29] These include laser-cutting, [16] molding, [30] and a few examples of 3D-printing of generic wings. [31,32] Although 3D-printing provides a straightforward way to mimic wings in nature and alter the wing design, [33][34][35] capturing the dynamic mechanical properties of insect wings remains a highly intricate problem. Developing insect-inspired artificial miniature wings for flapping drones thus continues to pose a challenge.…”
Section: Doi: 101002/adem202300861mentioning
confidence: 99%
“…The contribution by Zhilayev et al [18] investigates how artificial wings for flying robotic devices can be designed based on periodic honeycomb patterns. The authors start from the designs observed in insect wings and then use multi-parameter optimization to improve the flapping flight dynamics and the sound of a robotic drone.…”
Section: Metamaterials For Acoustic Control and Aerodynamic Propertiesmentioning
confidence: 99%